The relationship between adult phenylketonuria and the cardiovascular system - insights into mechanisms and risks - Yann Dos Santos; Friedrich Trefz; Maria Giżewska; Annemiek M.J. van Wegberg; Bruno Lefort; François Labarthe; Francjan van Spronsen; François Maillot (Orphanet Journal of Rare Diseases)
Abstract Studies in adults with PKU have mainly focused on the neuropsychiatric complications that may arise in individuals who are unable to maintain the recommended lifetime diet. Some recent epidemiological studies suggest to consider other complications. As such, cardiovascular (CV) issues have been the subject of few studies to date. The aim of this review is to gather and discuss data from the literature on the traditional risks of CV complications in PKU, a potential CV phenotype in this population and the various non-traditional risks and potential associated mechanisms. The reported prevalence of comorbidities suggests an increased risk of CV complications in adults with PKU, mostly in late-diagnosed patients. Studies about a specific CV phenotype associated with PKU are suggestive, although further studies are needed. The data on oxidative stress in this population are consistent and confirm an increased CV risk. Regarding other potential mechanisms, it is not possible to conclude whether adult PKU patients have low grade inflammation, dyslipidemia, kidney impairment or if they have hyperhomocysteinemia. It would be of interest to measure potential biomarker associated with CV complications, such as homocysteine, asymmetric dimethylarginine and kynurenines (quinolic acid).